IDDF2022-ABS-0206 Recurrence of advanced colorectal neoplasia in subjects with baseline non-advanced neoplasia: a comparison cohort study. (2nd September 2022) - Huang, Junjie; Leung, Eman; Chun, Sam; Deng, Yunyang; Lam, Thomas; Tang, Raymond; Wong, Martin
Abstract : Background: Although recent guidelines recommended a 5- to 10-year colonoscopy surveillance interval after a baseline finding of non-advanced neoplasia, there is little data to support this recommendation. In a large cohort, we examined the recurrence rate of advanced colorectal neoplasia after 5 years vs. 7–10 years among persons with non-advanced neoplasia identified and polypectomised at baseline colonoscopy. Methods: From a large database, we retrieved data from a large Chinese population with non-advanced neoplasia removed who had surveillance colonoscopy after 5 or 7–10 years (2008–2018). Recurrence of advanced colorectal neoplasia at surveillance colonoscopy was one of the outcome variables. The association between length of surveillance and the outcome variable was investigated using a binary logistic regression model that controlled for colorectal cancer contributing factors. Results: In our dataset, a total of 109, 768 patients who received a baseline colonoscopy were included. They were 67.35 years old on average, with 60.9 percent of them being male. Advanced colorectal neoplasia recurrence rates were 1.50 percent and 2.42 percent after 5 and 7–10 years, respectively (crude odds ratio=1.629, 95 percent C.I.1.362 to 1.949, p<0.001). According to the binary logistic regression model, people who had a surveillance colonoscopy at 7–10 years had a statistically higher recurrence rate of advanced colorectal neoplasia than those who were followed up at 5 years (adjusted odds ratio =1.544, 95 percent C.I. 1.266 to 1.877, p0.001), however, the effect size is minor. Conclusions: There is a minor difference in the recurrence of advanced colorectal neoplasia between people who had a colonoscopy at 5 years and those who had one at 7–10 years. After baseline non-advanced neoplasia was removed, our findings justify a 7–10 year surveillance interval.